A study article on the use of digital twin in the packaging industry - Deshpande, Manisha; Deshpande, Sameer (International Journal of Engineering and Technology, 2024)
After the COVID pandemic, the packaging requirements have ever growing due to the safety and security of the inside product. The total market value of packaging materials at a global level was nearly 896 billion U.S. dollars in 2022. It is forecast that this global market value will increase upto approximately 1.15 trillion U.S. dollars by 2030.1 In Industry 4.0; the workforce, machines, and processes are linked through digital networks.2 Data and Digital twin control production processes have emerged as a powerful tool. The digital twin has multiple advantages in the packaging sector, from cost and time savings to sustainable packaging development.